General principles of combating corruption in the countries of the Visegrad Four: the experience of the Czech Republic - V. S. Makarenko; O. S. Bakumov (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of the general principles of combating corruption in the territory of the Czech Republic. The fight against corruption, according to the Ministry of Regional Development of the Czech Republic, is a long-term process that requires the cooperation of all elements of the public administration system and includes prevention activities, transparency of all processes and the imposition of sanctions for violations. The purpose of the article is to study the experience of implementing anti-corruption activities on the territory of one of the countries of the Visegrad Group, namely the Czech Republic, establishing the path taken by the Czech Republic in the field of prevention and countering corruption, building its anti-corruption bodies, forming a strategy and clarifying the possibility of taking into account certain aspects in the activities of state bodies authorities and local self-government of Ukraine.